Analisis kesalahan siswa dalam menyelesaikan soal HOTS (higher order thinking skill) pada materi bangun datar kelas IV sekolah dasar - Felomina Loru; Trisniawati Trisniawati; Nelly Rhosyida (Universitas Sarjanawiyata Tamansiswa, 2023)
The research aims to describe: 1) the type of error that students do when solving HOTS (Higher Order Thinking Skills) questions and, 2) causes errors that students do when against HOTS (Higher Order Thinking Skills) questions in Kanisius Sang Timur Yogyakarta fourth grade elementary school student. This is qualitative descriptive research. The subject is Kanisius Sang Timur Yogyakarta fourth grade elementary school students. Miles and Huberman applied data analysis. Data collection techniques used are interview, observation, and test. The instruments study is HOTS question form of the descriptive amount four number of questions, interview guide for teachers and students, documentation, and observation guide. The tendency for error is in three parts. Concept error as much as 37,81%, operation error as much as 41,66%, and principle error as much as 30,76%. Conceptual errors that student do is not able to translate the question, and cannot use units according to two-Dimentional figures. Operational errors are, not carrying out calculations according to the proper settlement procedure, and the written final result is wrong. Principle error that is wrong in writing the formula, conclusion, and wrong placement of numbers according to the formula. Two factors are causing the error. An internal factor that is students are too hasty to solve the question so less careful in the process of solving the question and do not enough understand of the material of the two-dimension figure. An external factor is the impact of covid-19 pandemic, an environment that does not support the student learning process, and a lack of communication tool availability.